African diaspora and drum resistance: elements of the Yoruba society present in afro-Brazilian religions - Chagas, Wagner dos Santos (2020)
This text aims to present how Afro-Brazilian religions represent movements for the preservation and re-signification of the social structure of the Yoruba peoples in Brazil. The African diaspora, during the period of mercantile slavery, was responsible for the arrival in Brazil of millions of Africans from various ethnic groups such as the Bantu and the Yoruba. Afro-based religions represented a way to resist the destruction of the religious, social and cultural characteristics of these peoples. In the terreiro communities, a process of preservation and reframing of the social, cultural and religious structures of the Yoruba peoples was developed. The organization of worship, hierarchical structures, physical spaces, linguistic and cultural composition present in candomblé, Batuque or Nação, for example, have indelible marks of the Yoruba.